Revision of the complex of Echeta trinotata Reich, 1933: description of two new species (Lepidoptera: Erebiidae: Arctiinae) - Laguerre, Michel (Zootaxa, 2017)
Following a large survey of the Neotropical Arctiinae using the DNA barcodes technique (COI gene sequencing), Echeta trinotata Reich, 1933 was found to be in fact a complex of three cryptic highly genetically divergent species. The two new species are described as Echeta apatela sp. nov. from the foothills of the Andean Cordillera and Echeta rhodoptera sp. nov. from the Guianas shield, whereas the true Echeta trinotata is distributed along the lower Amazon from Manaus to Belém. Images of adults, male genitalia, genetic distance tree and distribution map are provided for the whole species group.